2011
DOI: 10.1590/s0103-50532011000800020
|View full text |Cite
|
Sign up to set email alerts
|

A multi-walled carbon nanotube-modified glassy carbon electrode as a new sensor for the sensitive simultaneous determination of paracetamol and tramadol in pharmaceutical preparations and biological fluids

Abstract: Um eletrodo modificado quimicamente foi construído, baseado em eletrodo de carbono vítreo modificado por nanotubos de carbono de parede múltipla (MWCNTs/GCE). Demonstrou-se que este sensor pode ser usado para a determinação simultânea de compostos com importância farmacêutica, como o paracetamol (PAR) e o tramadol (TRA). As medidas foram realizadas com aplicação de voltametria de pulso diferencial (DPV), voltametria cíclica (CV) e cronoamperometria (CA). A aplicação do método DPV demonstrou que em tampão fosfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Thus, it is necessary to develop methods of their determination in human body fluids. Last years, applications of electrochemical methods in determination and studies of drugs attract a lot of attention because of their accuracy and simplicity [9][10][11][12][13][14][15][16][17]. Electrochemical measurements enable determination of various physicochemical parameters of tested compounds, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is necessary to develop methods of their determination in human body fluids. Last years, applications of electrochemical methods in determination and studies of drugs attract a lot of attention because of their accuracy and simplicity [9][10][11][12][13][14][15][16][17]. Electrochemical measurements enable determination of various physicochemical parameters of tested compounds, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Von Mering first introduced PAR as an antipyretic/analgesic drug in 1893 , as a substitute for aspirin because it does not cause problems in patients who are prone to gastric issues. PAR is frequently found in association with other pharmaceuticals in the same formulation due to the synergic analgesic or supra additive effect of this combination, superior to each drug individually . PAR can be combined with orphenadrine (ORP), for the relief of muscle pain and in tension headaches ; with tramadol (TRA) to increase analgesia and reduce adverse events ; with codeine (COD) to treat acute pain and pyrexia ; with promethazine (PRO) as an antipyretic and antiemetic ; and with scopolamine (SCO) in therapy for gastrointestinal disorders such as colic .…”
Section: Introductionmentioning
confidence: 99%
“…Table I depicts a comparison of BDD electrode analytical performance created in this study with the other electroanalytical studies in earlier published report. As understood from this table, BDD electrode presented a more sensitive electroanalytical response than modified carbon paste electrode (M-CPE) 12 , coated wire electrode (CWE) 23 , carbon nanoparticles glassy carbon electrode (CNPs/GCE) 24 and multiwalled carbon nanotube glassy carbon (MWCNT/ /GCE) 25 electrodes. However, some electroanalytical studies 1, 3,13,14,[26][27][28][29] reported in the literature shown higher sensitivity than the developed method.…”
Section: Effect Of Anionic Surfactantmentioning
confidence: 86%